2023
DOI: 10.55782/ane-2023-003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varied‑intensity endurance exercise training on oxidative and antioxidant factors in the liver of rats with valproic acid‑induced autism

Abstract: Autism spectrum disorders are complex behavioral disorders that can be caused by exposure to valproic acid (VPA) during pregnancy. A therapeutic role for exercise training has been reported in many neurological diseases and problems, including autism. We aimed to evaluate various intensities of endurance exercise training and investigate its effects on oxidative and antioxidant factors in the liver of young males in a rat model of autism. Female rats were divided into a treatment (autism) and a control group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The etiology of ASD is not well understood [2,5], but it is likely that both biological and environmental factors are involved [6]. Biologically, genetic and nongenetic factors play a role, such as immunological and mitochondrial malfunction associated with oxidative stress, neurotrophic dysregulation and inflammation [7][8][9][10]. There is increasing evidence that ASD patients show excessive reactive oxygen species (ROS) production [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of ASD is not well understood [2,5], but it is likely that both biological and environmental factors are involved [6]. Biologically, genetic and nongenetic factors play a role, such as immunological and mitochondrial malfunction associated with oxidative stress, neurotrophic dysregulation and inflammation [7][8][9][10]. There is increasing evidence that ASD patients show excessive reactive oxygen species (ROS) production [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This animal model is considered a translational tool to evaluate potential therapies for ASD [18,19]. Recently, liver disorders have become a significant health concern and are an issue commonly found in autistic children [9,20]. Moreover, Trinchese et al [8] showed that inflammation and oxidative stress in these mice induce mitochondrial dysfunction and mitochondrial fission in the liver.…”
Section: Introductionmentioning
confidence: 99%